2014
DOI: 10.1007/s10068-014-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physicochemical characteristics and antioxidant activities of Jerusalem artichoke tea infusions resulting from different production processes

Abstract: The physicochemical properties of Jerusalem artichoke (Helianthus tuberosus L.) tea infusions produced using drying, roasting, puffing, and extrusion methods were investigated. The surfaces of puffed and extruded artichokes were more porous than the surfaces of dried and roasted artichokes. The water solubility index was highest for tea infusions of extruded and puffed artichokes. The total phenolic contents and antioxidant activities of artichoke tea infusions were in the order of puffed>extruded> roasted>hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The release of bioactive compounds from Jerusalem artichoke can be affected by processing. For instance, puffing and extrusion processes were recently found to increase the total phenolic content, free radical scavenging activity and ferric reducing antioxidant power of Jerusalem artichoke tea infusion compared to processing by roasting and hot air drying [99] . Moreover, a previous study showed that a combination of high hydrostatic pressure (HPP) and enzymatic treatments and fermentation increased the phenolic content and in vitro antioxidant (radical scavenging and superoxide-like) activities of Jerusalem artichoke tuber extract compared to water extraction [100] .…”
Section: Bioproducts Derived From Jerusalem Artichokementioning
confidence: 99%
“…The release of bioactive compounds from Jerusalem artichoke can be affected by processing. For instance, puffing and extrusion processes were recently found to increase the total phenolic content, free radical scavenging activity and ferric reducing antioxidant power of Jerusalem artichoke tea infusion compared to processing by roasting and hot air drying [99] . Moreover, a previous study showed that a combination of high hydrostatic pressure (HPP) and enzymatic treatments and fermentation increased the phenolic content and in vitro antioxidant (radical scavenging and superoxide-like) activities of Jerusalem artichoke tuber extract compared to water extraction [100] .…”
Section: Bioproducts Derived From Jerusalem Artichokementioning
confidence: 99%
“…They are powerful antioxidants and have been reported to demonstrate antibacterial, antiviral, anticarcinogenic, anti-inflammatory and vasodilatory actions [14][15][16][17]. The antioxidant activity of phenolic compounds extracted from JA tubers was confirmed in vitro using ORAC, FRAP and DPPH assays [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it contributes to the increased availability of such minerals as Fe, Mg, and Ca, and influences lipid metabolism [ 1 , 6 , 7 ]. Furthermore, JA improves immunity and concentration, alleviates stress, and eliminates toxic metabolites from the body [ 8 ]. Its main applications include the production of inulin [ 9 ], feedstuff, fructose syrup, flour, French fries, biochemical materials, and bioethanol [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%